PENGARUH KOMPENSASI DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. BLNP - Saing, Bungaran (JEMMA (Journal of Economic, Management and Accounting), 2025)
The purpose of this study was to determine simultaneously and partially the effect of compensation and workload on employee turnover intention at PT BLNP. The research sample of 94 people was selected using purposive sampling, while data collection used a questionnaire and the analysis technique used was two-stage regression analysis using SPSS version 23. The results showed that compensation had a significant effect on turnover intention, and workload had a significant effect on turnover intention, compensation and workload simultaneously had a significant effect on employee turnover intention.